2023
DOI: 10.1039/d2sc03754h
|View full text |Cite
|
Sign up to set email alerts
|

Selective and high-rate CO2 electroreduction by metal-doped covalent triazine frameworks: a computational and experimental hybrid approach

Abstract: The electrochemical CO2 reduction reaction (CO2RR) has attracted intensive attention as a technology to achieve a carbon-neutral society. The use of gas diffusion electrodes (GDEs) enables the realization of high-rate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 86 publications
(130 reference statements)
0
9
0
Order By: Relevance
“…Based on Brønsted Evans–Polanyi relations, , reactions with inferior Δ G values tend to face lesser energy barriers and are therefore more dynamically advantageous. In addition, recent studies have shown that only one adsorption strength (H* or COOH*) is needed to be used as a descriptor for the selectivity of HER, CO, and HCOOH. As shown in Figure , we consider the adsorption of OCOH* and OCHO* more carefully in the first step of CO 2 RR, which we think will give the reader a more complete understanding. Our calculation system is preferred to adsorb OCHO*, and HCOOH* is more likely to appear in the subsequent reaction than CO*, so we did not discuss the selectivity of HER, CO, and HCOOH in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Based on Brønsted Evans–Polanyi relations, , reactions with inferior Δ G values tend to face lesser energy barriers and are therefore more dynamically advantageous. In addition, recent studies have shown that only one adsorption strength (H* or COOH*) is needed to be used as a descriptor for the selectivity of HER, CO, and HCOOH. As shown in Figure , we consider the adsorption of OCOH* and OCHO* more carefully in the first step of CO 2 RR, which we think will give the reader a more complete understanding. Our calculation system is preferred to adsorb OCHO*, and HCOOH* is more likely to appear in the subsequent reaction than CO*, so we did not discuss the selectivity of HER, CO, and HCOOH in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…also serves as an effective approach to regulate the electrocatalytic CO 2 RR. [197][198][199][200] electrocatalytic CO 2 RR to CO with an FE of 97% at an applied potential of À0.9 V with a high current density of 52.9 mA cm À2 . 201 This excellent performance can be attributed to its atomically distributed NiN 4 centers (Fig.…”
Section: Electrochemical Energy Conversionmentioning
confidence: 99%
“…also serves as an effective approach to regulate the electrocatalytic CO 2 RR. 197–200 For example, Zhuang et al fabricated an Ni porphyrin-based CTF (NiPor-CTF) with atomically dispersed NiN 4 centers, which displayed great catalytic behaviors for electrocatalytic CO 2 RR to CO with an FE of 97% at an applied potential of −0.9 V with a high current density of 52.9 mA cm −2 . 201 This excellent performance can be attributed to its atomically distributed NiN 4 centers (Fig.…”
Section: Electrochemical Energy Storage and Conversion Applicationsmentioning
confidence: 99%
“…[14] Kato and coworkers have recently reported that Ni-CTFs showed both high selectivity (faradaic efficiency (FE) > 98 %) and a high reaction rate (current density > 200 mA cm À 2 ) for CO production. [15] On the basis of these findings, the Cu-modified CTFs (Cu-CTFs) stand out as potential materials for producing C 2 + compounds through the CO 2 RR, as well as for the reduction of CO derived from Ni-CTFs. However, as with Cu-CTFs, discussions that focus on the mechanism of CÀ C bond formation on Cu-SAECs have been largely absent.…”
Section: Introductionmentioning
confidence: 99%
“…These metal centers coordinate with the abundant isolated single electron pair of nitrogen in the pores, enabling a range of selective and unique electrocatalytic functions, such as the CO 2 RR, oxygen reduction, and nitrate reduction, through the selection of optimal metal species [14] . Kato and coworkers have recently reported that Ni‐CTFs showed both high selectivity (faradaic efficiency (FE) >98 %) and a high reaction rate (current density >200 mA cm −2 ) for CO production [15] . On the basis of these findings, the Cu‐modified CTFs (Cu‐CTFs) stand out as potential materials for producing C 2+ compounds through the CO 2 RR, as well as for the reduction of CO derived from Ni‐CTFs.…”
Section: Introductionmentioning
confidence: 99%